Update on Salvage Options in Relapsed/Refractory Hodgkin Lymphoma after Autotransplant. (30th March 2014) - Iqbal, Nida; Kumar, Lalit; Iqbal, Naveed
Abstract : Despite a high clinical success, relapse in Hodgkin lymphoma occurs in 10–30% of cases and 5–10% patients are nonresponsive to initial chemotherapy. The standard management of these patients includes high-dose chemotherapy followed by autologous stem cell transplant. However, 50% of patients ultimately relapse after autotransplant which poses a big challenge. Allogeneic stem cell transplantation offers the only chance of cure in these patients. For patients who are not candidates for allogeneic stem cell transplantation, achieving cure with other possible options is highly unlikely, and thus the treatment plan becomes noncurative. Various novel agents have shown promising results but the duration of response is short lived. A standard approach to deliver the most effective treatment for these patients is still lacking. This review focuses on the treatment options currently available for relapsed and refractory disease after autotransplant.